CORPORATE SOCIAL RESPONSIBILITY: BASIC CONCEPTS - Н. В. Орлова (Ринкова економіка: сучасна теорія і практика управління, 2016)
The article investigates the basic theoretical aspects and the most important scientific concepts of corporate social responsibility, the evolution of the concept. Corporate social responsibility is presented as a multi-level concept. Article discusses four groups of corporate social responsibility theories, considering their respective focus on four different aspects of the social reality: economics, politics, social integration, and ethics. The first one focuses on economics. Here the corporation is seen as an instrument for wealth creation. The second group focuses on the social power of the corporation and its responsibility in the political arena associated with its power. The third group focuses on social integration. It includes theories, which consider that business ought to integrate. Economic and legal obligations are primary and basic. In recent years, the ethical and philanthropic responsibilities have received more attention. Corporate social responsibility is a reflection of the fact that business and society are interwoven, so the business through the social responsibility system should play a significant role in the development of society, reflected in the concepts of “social state” and “socially-oriented economy”.